Strategi Digital Branding melalui Media Sosial dalam Mendorong Engagement dan Kinerja Usaha UMKM di Kalimantan Barat: Systematic Literature Review - Refor Diansyah; Resvan Resvan; Syukron Wahyudhi; Tari Indriani; Wulan Purnamasari; Nur Ainun (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study systematically reviews literature on Instagram-based digital branding strategies and their influence on engagement and business performance of MSMEs (UMKM) in West Kalimantan. It aims to identify key strategies, assess their effectiveness, and synthesize findings related to brand awareness, customer engagement, and business growth outcomes.The research adopts a Systematic Literature Review (SLR) using the PRISMA framework. Literature was sourced from Google Scholar, Scopus, and peer-reviewed journals on digital marketing and MSMEs. Findings show that Instagram digital branding improves engagement through visual content, storytelling, consistent posting, reels, live streaming, and hashtags. Higher engagement increases brand awareness, customer loyalty, and purchase decisions, leading to improved sales, market expansion, and revenue growth. However, limited digital literacy and weak content optimization remain major challenges for MSMEs.